2015
DOI: 10.1039/c5tc01650a
|View full text |Cite
|
Sign up to set email alerts
|

Graphite on paper as material for sensitive thermoresistive sensors

Abstract: We report on the thermoresistive properties of graphite on paper (GOP). A large temperature coefficient of resistance was observed and a highly sensitive GOP-based anemometer was demonstrated, indicating strong feasibility of using the GOP for low-cost thermoresistive sensors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 107 publications
(69 citation statements)
references
References 31 publications
2
65
0
2
Order By: Relevance
“…This can be attributed to the comparability of ionic and electronic polarizabilities of the substrate whose dielectric constant lies in the range of 2.5 to 10 (dielectric constant of paper ∼3 to 4) . In contrast, the graphitic resistive sensors exhibit high sensitivity to temperature . Therefore the graphite on paper capacitive sensor will exhibit stable response in comparison with resistive sensor despite the variation in surrounding temperature.…”
Section: Figuresupporting
confidence: 83%
“…This can be attributed to the comparability of ionic and electronic polarizabilities of the substrate whose dielectric constant lies in the range of 2.5 to 10 (dielectric constant of paper ∼3 to 4) . In contrast, the graphitic resistive sensors exhibit high sensitivity to temperature . Therefore the graphite on paper capacitive sensor will exhibit stable response in comparison with resistive sensor despite the variation in surrounding temperature.…”
Section: Figuresupporting
confidence: 83%
“…It is assumed that free carriers are trapped in the boundaries between graphite grains, creating a potential barrier which hinders the motion of carriers between graphite grains. Since the resistance of graphite grains is far smaller than that of the boundaries [17], the resistance of the graphite resistor can be approximated as boundary resistance, which is described as follows [18]: Journal of Sensors where k is the Boltzmann constant, φ is the potential barrier which impedes the motion of carriers between graphite grains, and T is the temperature. It is indicated that the application of the chemical substance increased the potential barrier.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the penciling direction is horizontal in the first cycle, vertical in the second cycle, and horizontal again in the third cycle . Employing such approach, SCs, humidity sensors, microfluidic devices, and anemometers have been demonstrated, in which pencil traces mainly acted as passive conductive elements. As is widely known, the dominating fillers in commercial pencils are graphite and clay, and the conductivity of the drawing trace is determined by the graphite content.…”
Section: Approaches To Boost Functionsmentioning
confidence: 99%